Medical abbreviations in school textbooks between formulation and usage – The Natural Sciences and Life textbook for the third year of secondary education as a model** - Ben Aarab, Fatiha; abesa, nabila (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : and their circulation in textbooks. To approach this problematic, I relied on the principle of collecting and extrapolating a sample of medical abbreviations used in the Algerian textbook scheduled to teach the subject of natural and life sciences for the third year of secondary school, experimental sciences division, through which I will try to shed light on two important issues, namely the issue of constructing the scientific abbreviation and the method of formulating it, and a second issue. It relates to the reality of its use in scientific textbooks, including extracting a set of findings and proposing some solutions.